Determinan Dukungan Keluarga Dengan Kejadian Relaps pada Pasien Skizofrenia Paranoid - Muhammad Ikhsan; Asri Bashir (NURSING UPDATE : Jurnal Ilmiah Ilmu Keperawatan P-ISSN : 2085-5931 e-ISSN : 2623-2871, 2023)
Schizophrenia is a mental disorder in which a person loses his mind and is unable to interact with other people. Therefore, family support is very important in the healing process of schizophrenic patients. Family support is an important factor in medication adherence in schizophrenic patients and therefore can have a positive impact on mental health. The purpose of this study was to see the relationship between family support and factors that influence the recurrence of schizophrenic patients. The type of research method used is correlational using a cross sectional design. sampling using the Incidental Sampling technique, namely as many as 90 respondents. The results of the study showed that the majority of schizophrenia patients relapsed frequently, namely 50 respondents (55.5%), family support based on low majority ratings, namely 46 respondents (52.3%), family support based on informational majority, low, namely 60 respondents (66.7%), family support based on emotional majority is high, namely 52 respondents (57.8%), family support based on instrumental is high, namely 51 respondents (56.7%), the results of cross-tabulation between family support and the incidence of relapse in schizophrenia patients, the results obtained are p -value of 0.001 with a significant level of p <0.05, the family support variable that influences relapse in schizophrenia patients is the category of emotional support with the highest Old Ratio (OR) value of 1.734. The most dominant factor for the frequency of relapse in schizophrenic patients is emotional support